2021
DOI: 10.1037/ccp0000546
|View full text |Cite
|
Sign up to set email alerts
|

Examining suicidal desire through the lens of the three-step theory: A cross-sectional and longitudinal investigation in a community sample.

Abstract: This study supports the validity and predictive utility of two steps of the Three-Step Theory of suicide in a community sample of adults. Pain, hopelessness, and connectedness exhibited moderate to strong relationships to current and future suicidal desire in a manner predicted by the theory. Findings suggest that the Three-Step Theory may be a useful perspective for guiding conceptualization and mitigation of suicidal desire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We used a three-item observational measure to assess clients’ initial suicidal desire. The three items were based on three of the items from the Beck Scale for Suicidal Ideation that loaded on the suicidal desire factor (Beck et al, 1997; Pachkowski et al, 2021) and were written in a way that face validly assessed suicidal desire: (a) desire to attempt, (b) desire to die, and (c) desire to live (reverse-scored). As has been previously noted (e.g., Pachkowski et al, 2021), solely using suicidal desire items unconfounds assessment from other aspects of SI (e.g., preparation).…”
Section: Methodsmentioning
confidence: 99%
“…We used a three-item observational measure to assess clients’ initial suicidal desire. The three items were based on three of the items from the Beck Scale for Suicidal Ideation that loaded on the suicidal desire factor (Beck et al, 1997; Pachkowski et al, 2021) and were written in a way that face validly assessed suicidal desire: (a) desire to attempt, (b) desire to die, and (c) desire to live (reverse-scored). As has been previously noted (e.g., Pachkowski et al, 2021), solely using suicidal desire items unconfounds assessment from other aspects of SI (e.g., preparation).…”
Section: Methodsmentioning
confidence: 99%
“…Higher total scores on the BSS-5 indicate more severe suicide ideation. The BSS-5 has demonstrated strong psychometric properties [ 39 , 40 ]. In the current study, the BSS-5 total score will be evaluated as an outcome variable.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the IPT, 3ST has not been tested as frequently on diverse populations; however, empirical evidence shows Steps 1 and 2 hypotheses apply to both men and women, across age groups (i.e., 18-25, 26-35, and 36-70;younger and older than 35;Dhingra et al, 2019;Klonsky & May, 2015) and in psychiatrically hospitalized adults (Tsai et al, 2021). Cross-sectional and longitudinal support of 3ST Steps 1 and 2 hypotheses has been demonstrated in a community sample of adults (Pachkowski et al, 2021). Importantly, a single study has tested 3ST hypotheses within college students (Dhingra et al, 2019) and found support for Step 1 (i.e., interaction of pain and hopelessness was associated with suicidal desire) and some aspects of Step 2 (i.e., social connectedness was protective against ideation in students high on both pain and hopelessness, but also students with other combinations of pain and hopelessness).…”
Section: Current Theories Of Suicidementioning
confidence: 99%